Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.706
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts for Agile User-Centered Design: A Systematic Mapping

Abstract: Abstract-The integration of Agile and User-Centered Design methods is a fundamental condition to improve the quality of software products. However, one of the main problems faced to establish this integration on a day-to-day basis is how to improve communication among the invariably distinct involved teams. We believe that the artifacts involved in the development process could be used to support and increase teams' communication.To better understand this scenario, we performed a systematic mapping study on ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…Our findings reveal that seven distinct artifacts were mentioned by Scrum Practitioners community members as facilitators in communication between designer and developer. Moreover, the results from Garcia et al [13] demonstrate that 20 artifacts accomplish this purpose. Therefore, to concentrate on the most used artifacts, we highlighted the intersection between this systematic mapping study and the findings herein presented (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Our findings reveal that seven distinct artifacts were mentioned by Scrum Practitioners community members as facilitators in communication between designer and developer. Moreover, the results from Garcia et al [13] demonstrate that 20 artifacts accomplish this purpose. Therefore, to concentrate on the most used artifacts, we highlighted the intersection between this systematic mapping study and the findings herein presented (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This mapping study [13] also revealed five distinct events involving artifacts used as communication mediators -Discovery, Planning, Iterative Cycle, Review Meeting, and General Meetings. The Iterative Cycle was the event with the greatest sharing of artifacts, and, in this event, Prototypes, and User Stories once again were the most cited artifacts.…”
Section: Artifacts In Aucdmentioning
confidence: 79%
See 2 more Smart Citations
“…Finally a solution model illustrates aspects of the future solution in a concrete model, such as a GUI mock-up or an abstract model, such as a data model. Garcia et al (2017) used a systematic mapping study to identify which artefacts are used in order to facilitate the communication in an agile user-centred design approach, but did not classify the resulting artefacts. Artefacts in both studies bear similarities to those in previously mentioned models, but are restricted to artefacts with regard to requirements and user-centred design respectively.…”
mentioning
confidence: 99%